2012
DOI: 10.1038/bjc.2012.365
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic importance of miR-21 in stage II colon cancer: a population-based study

Abstract: Background:Despite several years of research and attempts to develop prognostic models a considerable fraction of stage II colon cancer patients will experience relapse within few years from their operation. The aim of the present study was to investigate the prognostic importance of miRNA-21 (miR-21), quantified by in situ hybridisation, in a unique, large population-based cohort.Patients and methods:The study included 764 patients diagnosed with stage II colon cancer in Denmark in the year 2003. One section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 29 publications
6
67
1
1
Order By: Relevance
“…miRNA-21-5p was previously reported to show increased expression in tumor compared with normal colon mucosa (37), and was linked to early onset carcinogenesis (38). Two independent manuscripts reported that increased expression of miR21, predominantly in the stroma compartment and not the cancer cells, is associated with clinical outcome in TNM stage II colon cancer patients (39,40). These findings might explain why we did not see an association between miR21 expression and metastasis risk, unlike others (24).…”
Section: Discussioncontrasting
confidence: 41%
“…miRNA-21-5p was previously reported to show increased expression in tumor compared with normal colon mucosa (37), and was linked to early onset carcinogenesis (38). Two independent manuscripts reported that increased expression of miR21, predominantly in the stroma compartment and not the cancer cells, is associated with clinical outcome in TNM stage II colon cancer patients (39,40). These findings might explain why we did not see an association between miR21 expression and metastasis risk, unlike others (24).…”
Section: Discussioncontrasting
confidence: 41%
“…Down-regulation of miR-21 was associated with metastatic prostate cancer [55], although its over-expression has also been associated to tumor recurrence in colon [44][45][46], bladder [47], lung [48], breast [49,50] and even prostate cancer [51]. We were not able to find in the literature data associating miR-21 and recurrence in PTC, and we believe our study is the first one to identify miR-21 as a recurrence predictor for PTC.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 was one of the first miRNAs to be described as an oncomir. Upregulation of miR-21 is associated with a wide variety of cancers including tumor recurrence in colon [44][45][46], bladder [47], lung [48], breast [49,50] and prostate [51] cancers; and to lymph node metastasis in esophageal carcinoma [52][53][54]. However, a recent published paper associated the down-regulation of miR-21 to prostate cancer metastasis [55].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a total of 13 articles were identified as eligible studies (10,(16)(17)(18)(19)(29)(30)(31)(32)(33)(34)(35)(36). With our original study, 14 studies were finally included in the meta-analyses.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%